Understanding Muslim Young Consumers on Online Shopping: The role of Customer Review, Price, Trust and Security - Rokhman, Wahibur; Andiani, Fajar (EQUILIBRIUM, 2020)
Online shopping is an ubiquitous phenomenon among young consumers. The development of internet on transactions has caused fear, mistrust and risk among online consumers.  The objective of this study is to examine the effect of product reviews, prices, transaction trust, and security transactions on decisions in Islamic millennial generation online purchases. The sample in this study is the Muslim young generation who use a lot of online shoppings, a total of 120 respondents were requested to complete the questionnaires, of which 96 were returned using a purposive sampling technique with a minimum expenditure of spending 3 times in the last 3 months. The results of this study indicate that product reviews, prices, trust and security have significant effect on online purchasing decisions. This study also discusses the implications, limitations, and suggestions for the future research.